2013
DOI: 10.1016/j.dnarep.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of enzymatic interactions during short flap human Okazaki fragment processing by two forms of human DNA polymerase δ

Abstract: Lagging strand DNA replication requires the concerted actions of DNA polymerase δ, Fen1 and DNA ligase I for the removal of the RNA/DNA primers before ligation of Okazaki fragments. To better understand this process in human cells, we have reconstituted Okazaki fragment processing by the short flap pathway in vitro with purified human proteins and oligonucleotide substrates. We systematically characterized the key events in Okazaki fragment processing: the strand displacement, Pol δ/Fen1 combined reactions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 61 publications
(91 reference statements)
6
48
0
Order By: Relevance
“…We completed a contemporaneous analysis of the reactions involved in Okazaki fragment processing by both forms of Pol δ in cooperation with Fen1. 22 This study revealed that Pol δ3 possesses characteristics that are ideal for Okazaki fragment processing, further supporting the idea that it participates in DNA replication as well as in DNA repair.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…We completed a contemporaneous analysis of the reactions involved in Okazaki fragment processing by both forms of Pol δ in cooperation with Fen1. 22 This study revealed that Pol δ3 possesses characteristics that are ideal for Okazaki fragment processing, further supporting the idea that it participates in DNA replication as well as in DNA repair.…”
Section: Introductionsupporting
confidence: 53%
“…3, panel II). Our study of the combined actions of Pol δ3 and Fen1 shows that this is predominantly a nick translation process, while that of Pol δ4 and Fen1 presents as either a short flap pathway or a nick translation process that is dependent on the Fen1 concentration 22 (Fig. 3).…”
Section: 70mentioning
confidence: 99%
See 2 more Smart Citations
“…These include an increase in processivity, possibly because PDIP46 may stabilize Pol δ binding to PCNA by a bridging interaction, as well as by a direct activation that involves alteration of the kinetic properties of Pol δ4. The effects of PDIP46 were examined on model oligonucleotide templates [127] in assays that examined primer extension and strand displacement in order to gain insights into its mechanism(s) of action [56]. In the absence of PCNA, Pol δ4 behaves in a distributive fashion, and PDIP46 clearly stimulates this activity.…”
Section: Pdip46 Is a Potent Activator Of Pol δmentioning
confidence: 99%